Paediatric anti-N-methyl-d-aspartate receptor encephalitis: The first Italian multicenter case series. (July 2015) - Sartori, Stefano; Nosadini, Margherita; Cesaroni, Elisabetta; Falsaperla, Raffaele; Capovilla, Giuseppe; Beccaria, Francesca; Mancardi, Maria Margherita; Santangelo, Giuseppe; Giunta, Leandra; Boniver, Clementina; Cantalupo, Gaetano; Cappellari, Alberto; et al.
Abstract Background Given the rarity of this condition, especially in children, there is a paucity of large reported paediatric case series of anti-N-methyl-d-aspartate receptor encephalitis. Methods To contribute to define the features of this condition, we describe retrospectively a new nationwide case series of 20 children (50% females), referred by 13 Italian centres. Results Mean age at onset was 8 years (range 3–17). Prodromal symptoms were reported in 31.6%; onset was with neurological symptoms in 70%, and with behavioural/psychiatric disturbances in 30%. Most patients developed a severe clinical picture (90%), and 41% experienced medical complications; children 12–18 years old seemed to be more severe and symptomatic than younger patients. All children received first-line immune therapy; second-line treatment was administered to 45%. Relapses occurred in 15%. At last follow-up (mean 23.9 months, range 5–82), 85% patients had mRS 0–1; this rate was higher among older patients, and in those receiving first immune therapy within 1 month. Conclusions Our case series confirms a symptomatologic core of paediatric anti-N-methyl-d-aspartate receptor encephalitis, even though displaying some distinctive features that may be explained by a specific genetic background or by the limited number of patients. The growing incidence of this condition, the relative age-dependent variability of its manifestations, the availability of immunotherapy and the possible better outcome with early treatment impose a high index of clinical suspicion be maintained. In the absence of data suggesting other specific etiologies, paediatricians should consider this diagnosis for children presenting with neurological and/or behavioural or psychiatric disturbances, regardless of age and gender.